2015
DOI: 10.15226/2374-684x/2/3/00125
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Hemodynamic Effects of Alfaxalone and Propofol in Pigs

Abstract: Objective: The hemodynamic effects of alfaxalone and propofol on the cardiovascular system during anesthetic maintenance in experimental medicine were investigated in pigs using a Pulse Contour-Derived Cardiac Output (Picco) thermodilution monitoring device. Animals: In this prospective experimental study, six (alfaxalone) and seven (propofol) female Landrace pigs weighing 32.5±3.7 kg each were examined. Procedures: Sedation was induced by administering ketamine, azaperone and atropine intramuscularly, and ane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…In both ALF and EA-ALF groups, echocardiographic parameters fluctuated within the clinically acceptable with insignificant differences in SV and CO reported at alfaxalone MIR time. Prior studies revealed insignificant changes in CO, CI, and SV during alfaxalone anesthesia in goats [10], horses [41], and dogs [42,43]. In this current study, the alfaxaloneinduced tachycardia is most likely the compensatory reflex for maintaining CO within the normal level range throughout the experiment [10,44].…”
Section: Discussionmentioning
confidence: 47%
“…In both ALF and EA-ALF groups, echocardiographic parameters fluctuated within the clinically acceptable with insignificant differences in SV and CO reported at alfaxalone MIR time. Prior studies revealed insignificant changes in CO, CI, and SV during alfaxalone anesthesia in goats [10], horses [41], and dogs [42,43]. In this current study, the alfaxaloneinduced tachycardia is most likely the compensatory reflex for maintaining CO within the normal level range throughout the experiment [10,44].…”
Section: Discussionmentioning
confidence: 47%